Propaganda the formation of men's attitudes - Ellul, Jacques (New York Vintage Books, 1973)
From one of the greatest French philosophers of the 20th century, comes a seminal study and critique of propaganda. Taking not only a psychological approach, but a sociological approach as well, Ellul?s book outlines the taxonomy for propaganda, and ultimately, it?s destructive nature towards democracy. Drawing from his own experiences fighting for the French resistance against the Vichy regime, Ellul offers a unique insight into the propaganda machine.
Includes index
Keywords: Propaganda